2017
DOI: 10.1002/stem.2727
|View full text |Cite
|
Sign up to set email alerts
|

Survivin Is Required for Mouse and Human Bone Marrow Mesenchymal Stromal Cell Function

Abstract: Although mesenchymal stromal cells (MSCs) have significant potential in cell-based therapies, little is known about the factors that regulate their functions. While exploring regulatory molecules potentially involved in MSC activities, we found that the endogenous multifunctional factor Survivin is essential for MSC survival, expansion, lineage commitment, and migration. Pharmacological or genetic blockade of Survivin expression in mouse and human bone marrow MSC enhances caspase 3 and 7 expression and reduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…As a member of the IAP family, Birc5 is expressed in various cells including hematopoietic cells, immune cells and vascular endothelial cells, and mesenchymal stromal cells [4,17,18]. Additionally, Birc5 plays a role in regulating cell proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…As a member of the IAP family, Birc5 is expressed in various cells including hematopoietic cells, immune cells and vascular endothelial cells, and mesenchymal stromal cells [4,17,18]. Additionally, Birc5 plays a role in regulating cell proliferation and survival.…”
Section: Discussionmentioning
confidence: 99%
“…The expression is observed in all stages of interphase with exceptionally high expression in G2/M phase. Increased survivin expression protects MSCs that form HSCs supportive niche depleted post irradiation exposure [37]. The protein has been linked to survival in these cells subjected to stress induced by heat shock, UV or etoposide as well [38].…”
Section: Survivin In Stem Cellsmentioning
confidence: 99%
“…Furthermore, it has been shown that survivin inhibition in mouse and human bone marrow results in fewer MSC and clonogenic colony forming unit fibroblasts, whereas survivin overexpression in MSC promotes their proliferation; moreover, survivin inhibition in MSCs reduces their hematopoiesis-supporting capacity. According to the considerable role of MSCs in engraftment and maintenance of hematopoietic stem cell transplantation (HSCT), survivin-expressing MSCs seem to promote HSCT outcome [ 27 ]. In addition, erythrocytes have been demonstrated to be significantly dependent on survivin in their proliferation and maturation process, as heterozygous deletion of survivin in mice is accompanied by decreased number of enucleated erythrocytes and insufficient erythropoiesis while its complete deletion causes death [ 28 ].…”
Section: Survivin In Transplantationmentioning
confidence: 99%